2008
DOI: 10.1097/ijg.0b013e3181634f0f
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Central Corneal Thickness and Corneal Curvature Radius on The Intraocular Pressure as Measured By Different Tonometers: Noncontact and Goldmann Applanation Tonometers

Abstract: NCT can be more affected by CCT than GAT. CCR could influence the measurements of GAT, but not those by NCT. CCT and CCR can therefore influence the discordance of IOP readings taken with NCT and GAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 20 publications
3
38
0
1
Order By: Relevance
“…CCT measurement revealed that P2Y 6 KO mice showed thicker CCT at middle age. Many reports have suggested that IOP is positively correlated to CCT (67)(68)(69)(70)(71)(72)(73)(74)(75). Our present data demonstrated that mature adult P2Y 6 KO Figure 6.…”
Section: Discussionsupporting
confidence: 72%
“…CCT measurement revealed that P2Y 6 KO mice showed thicker CCT at middle age. Many reports have suggested that IOP is positively correlated to CCT (67)(68)(69)(70)(71)(72)(73)(74)(75). Our present data demonstrated that mature adult P2Y 6 KO Figure 6.…”
Section: Discussionsupporting
confidence: 72%
“…However, a few studies have reported a significant association between CCT and IOP among normotensive groups (Cho and Lam, 1999;Eysteinsson et al, 2002). Intraocular pressure measured by both non-contact tonometry (r = 0.515, p<0.0001) and Goldmann applanation tonometry (r = 0.237, p<0.05) was significantly correlated with CCT among normotensives (Harada et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…17 Harada ve ark.nın yaptığı bir diğer çalışmada, nonkontakt tonometre ve GAT ile yapılan ölçümlerde SKK ve korneal eğrilik yarıça-pının etkisi araştırılmış ve 526 µm sınır kabul edilerek oluşturulan iki gruptan kalın korneası olan grupta nonkontakt ve GAT ile alınan GİB değer-lerinin ince gruptakinden daha yüksek değerler olduğu ve kendi içinde değerlendirildiğinde nonkontakt tonometrik değerlerin SKK'den daha fazla etkilendiği saptanmıştır. 18 Öncel ve ark.nın çalış-masında, 60 sağlıklı bireyin nonkontakt tonometre, ORA, PDKT ve GAT ile GİB ölçümleri alınmış ve PDKT ile ORA ölçümlerinin SKK'den daha az etkilendiği belirtilmiştir. 19 Çalışmamızdan elde edilen GİB verilerinin analizi sonucunda özellikle ince korneası olan hastalarda Tono-Pen, PDKT veya Icare tonometresi ile yapılan ölçümlerin daha doğru GİB ölçüm sonucu verdiği gözlemlenmiştir.…”
Section: Discussionunclassified